IDENTIFYING THE TYPES OF ACCOUNTING TERMS IN ENGLISH ACCOUNTING BOOK AND THEIR EQUIVALENCES IN INDONESIAN - R. Guntur Mahardika; I Nyoman Sedeng; Ni Luh Nyoman Seri Malini (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2018)
Translation has important role to the development of science field, especially in accounting field which has been expanding in this globalization era. Hence, it is very interesting to analyze the translation of English accounting terms into Indonesian because it contains many accounting typical terms and specific vocabulary usually used by accountant. Furthermore, this research focuses on identifying of accounting terms in English accounting book and their equivalences in Indonesian. The data was collected by note taking and comparing techniques. Then, the data analysis is performed to search the form and category of the English accounting terms. Parallel corpora were used in presenting source language and target language data. Descriptive qualitative methods were applied to analyze all research problems. The theory of translation techniques proposed by Molina and Albir (2002) was applied in order to find translation techniques chosen by translator in translating English accounting terms and the theory of grammatical proposed by Quirk et al (1985) to find the categories of word, compound word and phrase. This research is expected to contribute to further research related to accounting vocabularies consist of a set of words, compound words and phrase which are considered available in all languages of the world.